Discovery of novel non-retroviral endogenous viral elements reveals their long-term integration history in spiders - Hengrui Hu; Just M. Vlak; Zhihong Hu; Manli Wang (Nature Communications)
Abstract Endogenous viral elements (EVEs) are widespread in the genomes of various organisms and have played a crucial role in evolution. Historically, research on EVEs primarily focused on those derived from retroviruses; however, the significance of non-retroviral EVEs (nrEVEs) has gradually gained recognition. In this study, we employ an approach that combines protein structure prediction with sequence analysis to identify a large group of previously unrecognized nrEVEs across spider genomes. Additionally, we identify nrEVE-related messenger RNAs, small interfering RNAs, and PIWI-interacting RNAs in spiders, suggesting that these nrEVEs may be functionally active. We also experimentally confirm the presence of spider nrEVEs and their transcripts in individual spiders. Evolutionary analysis suggests that these spider nrEVEs derived from unidentified nuclear arthropod large DNA viruses belonging to the order Lefavirales, class Naldaviricetes. Multiple integration events must have occurred both anciently and recently during the evolutionary history of spiders to explain these nrEVEs. Our findings reveal a novel group of nrEVEs and provide valuable insights into their evolutionary relationship with arthropods.